2011
DOI: 10.1016/j.anpedi.2011.01.012
|View full text |Cite
|
Sign up to set email alerts
|

Bronquiolitis grave. Cambios epidemiológicos y de soporte respiratorio

Abstract: Most patients admitted to the PICU are less than 3 months old. Mortality was 0.9%. Respiratory support (especially non-invasive mechanical ventilation and high flow nasal oxygen therapy) is used increasingly often. The youngest patients need more days in PICU and more respiratory support.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
3

Year Published

2015
2015
2019
2019

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 23 publications
0
4
0
3
Order By: Relevance
“…A wide variability exists in the use of different respiratory support techniques among countries 6,7 and even within the same country. 8,9 There is a lack of knowledge about the real value of each tool available for the management of respiratory failure in bronchiolitis. Recently, randomized controlled trials showed that early and generalized use of HFNC in mild-moderate bronchiolitis slightly reduced the percentage of pediatric ICU admissions.…”
Section: Introductionmentioning
confidence: 99%
“…A wide variability exists in the use of different respiratory support techniques among countries 6,7 and even within the same country. 8,9 There is a lack of knowledge about the real value of each tool available for the management of respiratory failure in bronchiolitis. Recently, randomized controlled trials showed that early and generalized use of HFNC in mild-moderate bronchiolitis slightly reduced the percentage of pediatric ICU admissions.…”
Section: Introductionmentioning
confidence: 99%
“…( 3 , 4 ) Higher risk of admission to pediatric ICU (PICU), need for mechanical ventilation (MV), long stay at the hospital, and death are associated with low weight, age under 30 days old, prematurity, congenital heart defect, chronic lung disease, and immunodeficiency. ( 3 , 5 , 6 ) AVB is a seasonal viral disease; the main etiologic agent is respiratory syncytial virus, which is present in more than 50% of the cases. ( 7 - 9 )…”
Section: Introductionmentioning
confidence: 99%
“…A idade média das crianças incluídas no nosso estudo foi de 1,88±1,25 meses. Estudo realizado na Espanha avaliou 229 pacientes internados em UTI pediátrica por BVA e constatou que a idade foi inversamente proporcional ao tempo necessário de suporte ventilatório e de dias de internação em UTI 18,19,20 . Um estudo realizado nos Estados Unidos apontou que de 1,1 milhão de crianças menores de dois anos internadas por VSR em um período de oito anos, a maior porcentagem das internações ocorreu na faixa etária entre três e seis meses 21 .…”
Section: Discussionunclassified